A LB-DF/FD Method for Particle Suspensions (Communications in Computational Physics, 2010)
In this paper, we propose a lattice Boltzmann (LB) method coupled with adirect-forcing fictitious domain (DF/FD) method for the simulation of particle suspensions.This method combines the good features of the LB and the DF/FD methodsby using two unrelated meshes, namely, an Eulerian mesh for the flow domain and aLagrangian mesh for the solid domain, which avoids the re-meshing procedure anddoes not need to calculate the hydrodynamic forces at each time step. The non-slipboundary condition is enforced by introducing a forcing term into the lattice Boltzmannequation, which preserves all remarkable advantages of the LBM in simulatingfluid flows. The present LB-DF/FD method has been validated by comparing its resultswith analytical results and previous numerical results for a single circular particleand two circular particles settling under gravity. The interaction between particle andwall, the process of drafting-kissing-tumbling (DKT) of two settling particles will bedemonstrated. As a manifestation of the efficiency of the present method, the settlingof a large number (128) of circular particles is simulated in an enclosure.